Partisipasi Lansia dalam Cek Kesehatan di Desa Mantang Baru - Juliana Eka Pratiwi; Dea Junartingsih; Ketryn Oktavia Ginting; Joko Apriadi; Jeremia Sitohang; Abdullah Ziyad Sulthany; Kamirul Kamirul; Jumi Candra; Zahra Vickryana; Jupita Natalia (Jurnal Pengabdian Masyarakat Waradin, 2025)
This study discusses the level of participation of elderly people in Mantang Baru Village in routine health checks. The main objective is to see how active they are in participating and what makes them interested or reluctant to attend health checks. This study uses a quantitative approach with the aim of measuring the level of participation of elderly people in health check activities in Mantang Baru Village. Data was collected using direct surveys of each elderly person's home, which contained questions related to the frequency of health check visits, motivation, and barriers to health checkups for the elderly. The population in this study was all elderly people aged 60 years and above who reside in Mantang Baru Village. The results showed that most elderly people were quite diligent in attending health checkups because they realized the importance of maintaining their physical condition. Factors such as family support, ease of access to health check locations, and their knowledge about health significantly influence their decision to participate. In conclusion, if health education and facilities can be further improved, elderly participation will certainly increase, thereby helping to maintain their health better. The role of health cadres is very significant in encouraging elderly participation through a personal approach and continuous education.